Financial Literacy In The MSME Sector - Moridu, Irwan (Journal of Management, 2023)
The purpose of this study was to evaluate the relationship between financial literacy, locus of control, and financial inclusion and the financial behaviour of MSME actors in the Central Market Environment of Luwuk Banggai Regency. The study was carried out with the help of SEM (Structural Equation Modelling) analysis tools and the PLS (Partial Least Square) approach on 55 samples of MSME actors. The findings of testing the hypothesis suggest that financial literacy and financial inclusion have a favourable impact on financial behaviour. Furthermore, financial literacy, locus of control, and financial inclusion all have an impact on financial behaviour. This demonstrates that financial literacy, locus of control, and financial inclusion all play a vital role in shaping the financial behaviour of MSME actors in the Luwuk Banggai Regency's Central Market Environment